Layer-by-layer self-assembly antistatic / flame-retardant fabric based on angular cross-linked structure and preparation method

Through layer-by-layer self-assembly method based on angular crosslinking structure, the materials such as DM ammonium alginate, PB phytic acid and dopamine hydrochloride are impregnated layer by layer, and the problem of flame retardant and antistatic properties of cotton fabrics is solved, achieving efficient flame retardant and Anti-static effect while improving the durability and comfort of the fabric.

CN119392501APending Publication Date: 2025-02-07YULIN LUXURY CLOTHING TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411601516.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

While the prior art imparts flame retardant and antistatic properties to cotton fabrics, there are problems such as performance balance problems, durability and comfort influences.

Method used

Using a layer-layer self-assembly method based on the angular crosslinking structure, the angular crosslinking mild gel structure and conductive layer are formed by impregnating materials such as DM ammonium alginate, PB phytic acid and dopamine hydrochloride layer by layer to enhance the flame retardant and resistance of the fabric. Electrostatic properties.

Benefits of technology

The effective balance between flame retardant properties and antistatic properties of cotton fabrics is achieved, which enhances the durability and conductive properties of the fabric without affecting the comfort of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392501A_ABST
    Figure CN119392501A_ABST
Patent Text Reader

Abstract

The invention discloses a layer-by-layer self-assembled antistatic / flame-retardant fabric based on an angular cross-linked structure and a preparation method thereof, and the preparation method specifically comprises the following steps: dipping a cotton fabric in a mixed solution of a DM-ammonium alginate solution, drying, dipping the obtained cotton fabric in a mixed solution of a PB-phytic acid solution, drying, and drying to obtain the layer-by-layer self-assembled antistatic / flame-retardant fabric. Dipping the obtained cotton fabric in a dopamine hydrochloride solution, assembling layer by layer, and drying; and immersing the cotton fabric into the pyrrole solution, dropwise adding an initiator into the pyrrole solution to polymerize pyrrole, stirring, and drying. The DM ammonium alginate is used for isolating phytic acid from damaging the cotton fabric, and meanwhile the isolating layer is endowed with the flame retardant property; secondly, phosphorus-containing polybasic carboxylic acid PB phytic acid and DM ammonium alginate are cross-linked, the antistatic / flame-retardant fabric with a corner cross-linked molecular structure is obtained, and a corner cross-linked slight gel structure is constructed. Finally, dopamine and pyrrole are polymerized and assembled on the surface of the fabric layer by layer, so that the fabric has conductivity, and the fabric has antistatic performance while the flame retardant property is not affected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fabric preparation, and in particular relates to a method for preparing a layer-by-layer self-assembled antistatic / flame-retardant fabric based on an angular cross-linked structure, and also relates to the layer-by-layer self-assembled antistatic / flame-retardant fabric. Background Art

[0002] Static electricity is generated by processes such as friction between objects. It may cause serious accidents in industries such as petrochemicals, and affect product quality in the electronics industry. Antistatic methods include conductive fiber addition and fabric finishing, but there is a balance between the amount added and performance, cost, and washing durability. Fabric combustion is a complex thermal oxidation process. The principle of flame retardancy is to interrupt the combustion link. The methods include flame retardant fiber method and flame retardant finishing method. However, the existing technology has limitations in the balance of antistatic and flame retardant properties, durability, and the impact on comfort and physical properties. For example, conductive fibers may be incompatible with flame retardants, finishing agents affect static electricity conduction, performance is affected by environmental factors and may change the feel of the fabric.

[0003] The use of post-finishing methods to impart flame retardant and antistatic properties to cotton fabrics is a technology involving a variety of materials and processes. In terms of flame retardant properties, by selecting flame retardants such as phosphorus or nitrogen, cotton fabrics are immersed in flame retardant solutions by the dipping method, or flame retardants and adhesives are mixed and coated on the fabric surface by the coating method. In terms of antistatic properties, surfactants, polymer permanent antistatic agents, etc. are selected to treat cotton fabrics by dipping, spraying, etc., so that a conductive layer is formed on the surface of the fabric or conductive groups are introduced, so that the fabric has antistatic ability. This post-finishing method needs to consider a variety of factors comprehensively, so as to achieve flame retardant and antistatic properties of cotton fabrics while minimizing the impact on their original properties, and ensuring the durability and stability after treatment. However, the research on making cotton fabrics have both flame retardant and antistatic properties by post-finishing means is not mature, and there are cases where the coating is easy to fall off and the two properties affect each other. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a layer-by-layer self-assembled antistatic / flame-retardant fabric based on an angular cross-linked structure, wherein the fabric has high flame retardant and antistatic properties.

[0005] Another object of the present invention is to provide a layer-by-layer self-assembled antistatic / flame retardant fabric based on an angular cross-linked structure.

[0006] The technical solution adopted by the present invention is a method for preparing a layer-by-layer self-assembled antistatic / flame-retardant fabric based on an angular cross-linked structure, which is specifically implemented according to the following steps: Step 1, immersing cotton fabric in a mixed solution of DM-ammonium alginate solution, and drying, to prepare cotton fabric containing gel-like DM ammonium alginate; Step 2, immersing the cotton fabric obtained in step 1 in a mixed solution of PB-phytic acid solution, and drying to prepare a cotton fabric with an angularly cross-linked slight gel structure; Step 3, immersing the cotton fabric obtained in step 2 in a dopamine hydrochloride solution to assemble layer by layer, and drying; immersing the cotton fabric in a pyrrole solution, and dropping an initiator into the pyrrole solution to polymerize the pyrrole, performing ultrasonic stirring, and drying to obtain a layer-by-layer self-assembled antistatic / flame retardant fabric based on an angular cross-linked structure.

[0007] The present invention is also characterized in that: In step 1, the immersion time is 20-60 minutes, the ammonium alginate solution is composed of ammonium alginate and deionized water; the volume ratio of the ammonium alginate solution to DM is 10-20:1; and the mass fraction of the ammonium alginate solution is 2%-5%.

[0008] DM is dimethyl N, N-bis (2-hydroxyethyl phosphoramide); the preparation process of dimethyl N, N-bis (2-hydroxyethyl phosphoramide) is as follows: Tetrahydrofuran, dimethyl phosphite and diethanolamine were mixed in a volume ratio of 4:2:3, stirred for 1 hour, the white precipitate was filtered out and dried to obtain light yellow dimethyl N,N-bis(2-hydroxyethylphosphoramide).

[0009] In step 2, PB is 2-phosphonobutane-1,2,4-tricarboxylic acid; the phytic acid solution is composed of phytic acid and deionized water; the volume ratio of the phytic acid solution to PB is 10:2-5; and the mass fraction of the phytic acid solution is 5%-10%.

[0010] In step 2, the immersion time is 20 minutes to 6 hours.

[0011] In step 3, the immersion time is 20-60 minutes. The drying temperature is 40°C-80°C, the drying time is 2h, and the ultrasonic time is 2-4h.

[0012] In step 3, the dopamine hydrochloride solution is composed of dopamine hydrochloride powder and deionized water; the concentration of the dopamine hydrochloride solution is 5%-15%; The initiator is a ferric chloride solution, and the concentration of the ferric chloride solution is 0.2 mol / L-1 mol / L; the concentration of the pyrrole solution is 1%-5%.

[0013] Another technical solution adopted by the present invention is a layer-by-layer self-assembled antistatic / flame-retardant fabric prepared by a method for preparing layer-by-layer self-assembled antistatic / flame-retardant fabric with an angular cross-linked structure.

[0014] The beneficial effects of the present invention are: The present invention adopts a fabric with an angular cross-linked structure constructed by a layer-by-layer impregnation assembly method, and uses a dimethyl N, N-bis (2-hydroxyethyl phosphoramide) / ammonium alginate (DM ammonium alginate) composite material to isolate phytic acid from damaging cotton fabrics while giving the insulation layer flame retardant properties. Secondly, 2-phosphonobutane-1,2,4-tricarboxylic acid is introduced into phytic acid to obtain phosphorus-containing polycarboxylic acid PB phytic acid, which is cross-linked with DM ammonium alginate. The molecular chains between the gel-like insulation layer and the phosphorus-containing polycarboxylic acid flame retardant layer will form an angle cross-linking to obtain an antistatic / flame retardant fabric with an angular cross-linked molecular structure, enhance the molecular chain bonding strength between the two layers of functional coatings, and construct an angular cross-linked slight gel structure. Finally, dopamine and pyrrole are polymerized layer by layer and assembled on the surface of the fabric to make the fabric conductive, so that the fabric has antistatic properties without affecting the flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 A schematic diagram of the self-assembly of the layer-by-layer self-assembled antistatic / flame-retardant fabric based on the angular cross-linked structure of the present invention is given. DETAILED DESCRIPTION

[0016] The present invention is described in detail below in conjunction with specific implementation modes and accompanying drawings.

[0017] The preparation method of the layer-by-layer self-assembled antistatic / flame-retardant fabric based on the angular cross-linked structure of the present invention adopts gel-like DM ammonium alginate and composite flame retardant PB phytic acid to perform flame retardant finishing on cotton fabric to form a gel-like "angular cross-linked" three-dimensional structure, and adopts polypyrrole and cotton fabric embedded structure construction to perform antistatic finishing on cotton fabric.

[0018] Follow the steps below to implement it: Step 1, immersing cotton fabric in a mixed solution of DM-ammonium alginate solution for 20-60 minutes, and drying to prepare cotton fabric containing gel-like DM ammonium alginate; DM is dimethyl N,N-bis(2-hydroxyethylphosphoramide); The preparation process of dimethyl N,N-bis(2-hydroxyethylphosphoramide) is as follows: Tetrahydrofuran, dimethyl phosphite and diethanolamine were mixed in a volume ratio of 4:2:3, stirred for 1 hour, the white precipitate was filtered out and dried to obtain light yellow dimethyl N,N-bis(2-hydroxyethylphosphoramide); The volume ratio of ammonium alginate solution to DM is 10-20:1; the ammonium alginate solution is composed of ammonium alginate and deionized water; the mass fraction of the ammonium alginate solution is 2%-5%; Step 2, immersing the cotton fabric obtained in step 1 in a mixed solution of PB-phytic acid solution for 20 minutes to 6 hours, and drying to prepare a cotton fabric with an angularly cross-linked slight gel structure; PB is 2-phosphonobutane-1,2,4-tricarboxylic acid; The volume ratio of the phytic acid solution to PB is 10:2-5; the phytic acid solution is composed of phytic acid and deionized water; the mass fraction of the phytic acid solution is 5%-10%; and the purity of the phytic acid is 20%-80%.

[0019] Dimethyl N, N-bis (2-hydroxyethyl phosphoramide) / ammonium alginate (DM ammonium alginate) composite material is used to give the insulation layer flame retardant properties on the basis of isolating phytic acid. 2-phosphonobutane-1,2,4-tricarboxylic acid is introduced into phytic acid to obtain phosphorus-containing polycarboxylic acid PB phytic acid, which is cross-linked with DM ammonium alginate to construct an angular cross-linked slight gel structure to enhance flame retardancy and durability.

[0020] Step 3, immersing the cotton fabric obtained in step 2 in a dopamine hydrochloride solution with a concentration of 5%-15% and assembling layer by layer, the immersion time is 20-60 minutes, and drying the cotton fabric at a temperature of 40°C-80°C for 2 hours, so that a layer of nano adhesive is formed on the surface of the internal fibers of the cotton fabric; immersing the dried cotton fabric in a pyrrole solution with a concentration of 1%-5%, and dropping an initiator into the pyrrole solution to polymerize the pyrrole, and performing ultrasonic stirring for 2-4 hours; drying the obtained cotton fabric at 40°C-80°C for 2 hours, so as to obtain a layer-by-layer self-assembled antistatic / flame retardant fabric based on an angular cross-linking structure; The dopamine hydrochloride solution is composed of dopamine hydrochloride powder and deionized water; The initiator is ferric chloride solution with a concentration of 0.2 mol / L-1 mol / L.

[0021] The purity of pyrrole solution is above 99%.

[0022] Dopamine and pyrrole polymers are assembled layer by layer on the surface of the fabric to make the fabric conductive and have antistatic properties without affecting the flame retardant properties.

[0023] In the method of the present invention, dimethyl N, N-bis (2-hydroxyethyl phosphoramide) and alginate chemical reagents are selected as isolating agents for isolating flame retardants from damaging fabrics. A mixed solution of 2-phosphonobutane-1,2,4-tricarboxylic acid and phosphorus-based flame retardants is used as a flame retardant agent for cotton fabrics. The molecular chains between the gel-like insulating layer and the phosphorus-containing polycarboxylic acid flame retardant layer will form an angle crosslinking to obtain an angle crosslinking molecular structure, thereby enhancing the molecular chain bonding strength between the two functional coating layers. Dopamine is then used to form a nano-scale adhesive layer on the fiber surface inside the fabric, and is impregnated and self-assembled with polypyrrole layer by layer to prepare a conductive polymer with high adhesion properties.

[0024] Example 1 Taking a 15*15cm plain weave cotton fabric with a thickness of 0.4mm as an example): a layer-by-layer self-assembled antistatic / flame-retardant fabric based on an "angular cross-linking" structure 4 composed of a DM ammonium alginate insulation layer 1, a PB phytic acid flame-retardant layer 2 and a polypyrrole conductive layer 3, the manufacturing process is as follows: 1) Material selection: The fabric base material is selected as a cotton fabric with a fabric size of 15*15cm, a plain weave, and a fabric thickness of 0.4mm. Dimethyl N, N-bis (2-hydroxyethyl phosphoramide) (DM) composite alginate ammonium solution is used as the insulation layer, and the flame retardant layer is selected as a phosphorus-containing polycarboxylic acid, that is, 2-phosphonic acid butane-1,2,4-tricarboxylic acid (PB) and phytic acid. The insulation layer and the flame retardant layer can form an angled cross-linking through the molecular chain to obtain an "angle cross-linking" molecular structure, which enhances the molecular chain bonding strength between the two functional coatings. The conductive layer material uses ferric chloride to guide the polymerization of pyrrole to form a conductive polymer polypyrrole, and through dopamine nanobonding, the polypyrrole is embedded in the fabric.

[0025] 2) Preparation of flame retardant isolation solution: Dissolve powdered ammonium alginate in deionized water, stir at room temperature for 3 hours, and prepare a 2% ammonium alginate solution. Prepare a mixed solution with a volume ratio of ammonium alginate to DM of 20:1. The total volume of the mixed solution is 50 ml.

[0026] 3) Initial impregnation of cotton fabric to form an insulating layer: Immerse the alkali-treated fabric in the prepared DM alginate solution for 20 minutes, squeeze out the excess solution in the fabric, and o Dry at C for 2 hours.

[0027] 4) Preparation of flame retardant: Add deionized water to the solution of phosphorus flame retardant, stir at room temperature for 30 minutes, prepare phytic acid solution with a concentration of 8%, and prepare a mixed solution according to the volume ratio of phytic acid to PB of 10:5. The total amount of solution is 50ml to fully immerse the fabric. In the mixed solution, the higher the proportion of phytic acid, the more obvious the "angle cross-linking" structure is.

[0028] 5) Secondary impregnation of cotton fabric to form a flame retardant layer: The cotton fabric that has been impregnated with DM alginate solution and dried is immersed in the prepared PB phytic acid solution for 30 minutes, the excess solution in the fabric is squeezed out and the flame retardant layer is formed at 40 o C for 2 hours. With the increase of immersion time in PB phytic acid solution, the flame retardant property of cotton fabric becomes stronger and stronger. After burning for 17 seconds, the damaged length of fabric is only 2 cm.

[0029] 6) Preparation of antistatic finishing solution: Take dopamine hydrochloride powder and add deionized water to prepare a 5% dopamine hydrochloride solution. Dissolve the pyrrole solution in deionized water and dilute it to prepare a 1% pyrrole solution. Dilute the initiator for pyrrole polymerization with deionized water to prepare an initiator with a concentration of 0.2 mol / L. 100 ml of 1% pyrrole solution and 10 ml of 0.2 mol / L ferric chloride solution are required.

[0030] 7) Dip the cotton fabric three times to form a conductive layer: Dip the flame-retardant treated cotton fabric into the prepared dopamine hydrochloride solution for 20 minutes and then o Dry at room temperature for 2 hours. As the immersion time increases, the thickness of the nano-adhesive layer increases and the adhesive performance becomes stronger. Then immerse the fabric in a 1% pyrrole solution, slowly drop the prepared initiator and stir. The higher the concentration of the pyrrole solution, the better the conductivity of the polypyrrole. Ultrasonicate at room temperature for 2 hours. Squeeze the excess solution from the treated fabric and place it at 40 o C for 2 hours; the final measured point-to-point resistance of the fabric is 2.2×10 5 Ω.

[0031] The method of the present invention is to impregnate the DM ammonium alginate solution and the PB phytic acid solution layer by layer, so that a microgel structure appears on the surface of the cotton fabric, and the flame retardant performance of the fabric is achieved while enhancing the adhesion between the reagent and the fabric. Secondly, dopamine and pyrrole are polymerized and assembled layer by layer on the fabric surface to make the fabric conductive, so that the fabric has antistatic properties without affecting the flame retardant properties.

[0032] Example 2 Taking a 15*15cm plain weave structure with a thickness of 0.6mm polyester-cotton (13:7) fabric as an example): a layer-by-layer self-assembled antistatic / flame-retardant fabric based on an "angular cross-linking" structure 4 composed of a DM ammonium alginate insulation layer 1, a PB phytic acid flame-retardant layer 2 and a polypyrrole conductive layer 3, the manufacturing process is as follows: 1) Material selection: The fabric base material is a polyester-cotton (13:7) fabric with a fabric size of 15*15cm, a plain weave, and a fabric thickness of 0.6mm. Dimethyl N,N-bis(2-hydroxyethylphosphoramide) (DM) composite alginate ammonium solution is used as the insulation layer, and the flame retardant layer is a phosphorus-containing polycarboxylic acid, that is, 2-phosphonobutane-1,2,4-tricarboxylic acid (PB) and phytic acid. The insulation layer and the flame retardant layer can form an angled cross-linking through the molecular chain to obtain an "angle cross-linking" molecular structure, which enhances the molecular chain bonding strength between the two functional coatings. The conductive layer material uses ferric chloride to guide the polymerization of pyrrole to form a conductive polymer polypyrrole, and through dopamine nanobonding, the polypyrrole is embedded in the fabric.

[0033] 2) Preparation of flame retardant isolation solution: Dissolve powdered ammonium alginate in deionized water, stir at room temperature for 3 hours, and prepare a 4% ammonium alginate solution. Prepare a mixed solution with a volume ratio of ammonium alginate to DM of 10:1. The total volume of the mixed solution is 50 ml.

[0034] 3) Initial impregnation of polyester-cotton fabric to form an insulating layer: Immerse the alkali-treated fabric in the prepared DM alginate solution for 40 minutes, squeeze out the excess solution in the fabric, and o Dry at C for 2 hours.

[0035] 4) Preparation of flame retardant: Add deionized water to the solution of phosphorus flame retardant, stir at room temperature for 30 minutes, prepare phytic acid solution with a concentration of 6%, and prepare a mixed solution according to the volume ratio of phytic acid to PB of 10:2. The total amount of solution is 50ml to fully immerse the fabric.

[0036] 5) Secondary impregnation of cotton fabric to form a flame retardant layer: The cotton fabric that has been impregnated with DM alginate solution and dried is immersed in the prepared PB phytic acid solution for 2 hours, the excess solution in the fabric is squeezed out and the flame retardant layer is formed at 40 o C for 2 hours. With the increase of immersion time in PB phytic acid solution, the flame retardant property of cotton fabric becomes stronger and stronger. After burning for 10 seconds, the damaged length of fabric is 2.5 cm.

[0037] 6) Preparation of antistatic finishing solution: Take dopamine hydrochloride powder and add deionized water to prepare a 5% dopamine hydrochloride solution. Dissolve the pyrrole solution in deionized water and dilute it to prepare a 2% pyrrole solution. Dilute the initiator for pyrrole polymerization with deionized water to prepare an initiator with a concentration of 0.4 mol / L. 100 ml of 2% pyrrole solution and 10 ml of 0.4 mol / L ferric chloride solution are required.

[0038] 7) Dip the cotton fabric three times to form a conductive layer: Dip the flame-retardant treated cotton fabric into the prepared dopamine hydrochloride solution for 30 minutes and then o Dry at room temperature for 2 hours. As the immersion time increases, the thickness of the nano-adhesive layer increases and the adhesive performance becomes stronger. Then immerse the fabric in a 2% pyrrole solution, slowly drop the prepared initiator and stir. The higher the concentration of the pyrrole solution, the better the conductivity of the polypyrrole. Ultrasonicate at room temperature for 2 hours. Squeeze the excess solution from the treated fabric and place it at 40 o C for 2 hours, and the final point-to-point resistance of the fabric was 8.3×10 4 Ω.

[0039] Example 3 The preparation method of the layer-by-layer self-assembled antistatic / flame-retardant fabric based on the angular cross-linked structure of the present invention is specifically implemented according to the following steps: Step 1, immersing cotton fabric in a mixed solution of DM-ammonium alginate solution for 30 minutes, and drying to prepare cotton fabric containing gel-like DM ammonium alginate; DM is dimethyl N,N-bis(2-hydroxyethylphosphoramide); The preparation process of dimethyl N,N-bis(2-hydroxyethylphosphoramide) is as follows: Tetrahydrofuran, dimethyl phosphite and diethanolamine were mixed in a volume ratio of 4:2:3, stirred for 1 hour, the white precipitate was filtered out and dried to obtain light yellow dimethyl N,N-bis(2-hydroxyethylphosphoramide); The volume ratio of ammonium alginate solution to DM is 15:1; the ammonium alginate solution is composed of ammonium alginate and deionized water; the mass fraction of the ammonium alginate solution is 2%; Step 2, immersing the cotton fabric obtained in step 1 in a mixed solution of PB-phytic acid solution for 1 hour, and drying to prepare a cotton fabric with an angularly cross-linked slight gel structure; PB is 2-phosphonobutane-1,2,4-tricarboxylic acid; The volume ratio of the phytic acid solution to PB is 10:2; the phytic acid solution consists of phytic acid and deionized water; the mass fraction of the phytic acid solution is 5%; and the purity of the phytic acid is 20%.

[0040] Step 3, immersing the cotton fabric obtained in step 2 in a 5% dopamine hydrochloride solution for layer-by-layer assembly, the immersion time is 20 minutes, and drying the cotton fabric at 40°C for 2 hours, so that a layer of nano adhesive is formed on the surface of the internal fibers of the cotton fabric; immersing the dried cotton fabric in a 1% pyrrole solution, and dropping an initiator into the pyrrole solution to polymerize the pyrrole, and performing ultrasonic stirring for 2 hours; drying the obtained cotton fabric at 40°C for 2 hours, so as to obtain a layer-by-layer self-assembled antistatic / flame retardant fabric based on an angular cross-linking structure; The dopamine hydrochloride solution is composed of dopamine hydrochloride powder and deionized water; the initiator is ferric chloride solution with a concentration of 0.2 mol / L.

[0041] Example 4 The preparation method of the layer-by-layer self-assembled antistatic / flame-retardant fabric based on the angular cross-linked structure of the present invention is specifically implemented according to the following steps: Step 1, immersing cotton fabric in a mixed solution of DM-ammonium alginate solution for 35 minutes, and drying to prepare cotton fabric containing gel-like DM ammonium alginate; DM is dimethyl N,N-bis(2-hydroxyethylphosphoramide); The preparation process of dimethyl N,N-bis(2-hydroxyethylphosphoramide) is as follows: Tetrahydrofuran, dimethyl phosphite and diethanolamine were mixed in a volume ratio of 4:2:3, stirred for 1 hour, the white precipitate was filtered out and dried to obtain light yellow dimethyl N,N-bis(2-hydroxyethylphosphoramide); The volume ratio of ammonium alginate solution to DM is 10:1; the ammonium alginate solution is composed of ammonium alginate and deionized water; the mass fraction of the ammonium alginate solution is 2.5%; Step 2, immersing the cotton fabric obtained in step 1 in a mixed solution of PB-phytic acid solution for 1.5 hours, and drying to prepare a cotton fabric with an angularly cross-linked slight gel structure; PB is 2-phosphonobutane-1,2,4-tricarboxylic acid; The volume ratio of the phytic acid solution to PB is 10:3; the phytic acid solution consists of phytic acid and deionized water; the mass fraction of the phytic acid solution is 6%; and the purity of the phytic acid is 40%.

[0042] Step 3, immersing the cotton fabric obtained in step 2 in a 10% dopamine hydrochloride solution for layer-by-layer assembly, the immersion time is 40 minutes, and drying the cotton fabric at 50°C for 2 hours, so that a layer of nano adhesive is formed on the surface of the internal fibers of the cotton fabric; immersing the dried cotton fabric in a 2.5% pyrrole solution, and dropping an initiator into the pyrrole solution to polymerize the pyrrole, and performing ultrasonic stirring for 3 hours; drying the obtained cotton fabric at 60°C for 2 hours, so as to obtain a layer-by-layer self-assembled antistatic / flame retardant fabric based on an angular cross-linking structure; The dopamine hydrochloride solution is composed of dopamine hydrochloride powder and deionized water; the initiator is ferric chloride solution with a concentration of 0.5 mol / L.

[0043] Example 5 The preparation method of the layer-by-layer self-assembled antistatic / flame-retardant fabric based on the angular cross-linked structure of the present invention is specifically implemented according to the following steps: Step 1, immersing cotton fabric in a mixed solution of DM-ammonium alginate solution for 50 minutes, and drying to prepare cotton fabric containing gel-like DM ammonium alginate; DM is dimethyl N,N-bis(2-hydroxyethylphosphoramide); The preparation process of dimethyl N,N-bis(2-hydroxyethylphosphoramide) is as follows: Tetrahydrofuran, dimethyl phosphite and diethanolamine were mixed in a volume ratio of 4:2:3, stirred for 1 hour, the white precipitate was filtered out and dried to obtain light yellow dimethyl N,N-bis(2-hydroxyethylphosphoramide); The volume ratio of ammonium alginate solution to DM is 18:1; the ammonium alginate solution is composed of ammonium alginate and deionized water; the mass fraction of the ammonium alginate solution is 3.5%; Step 2, immersing the cotton fabric obtained in step 1 in a mixed solution of PB-phytic acid solution for 4 hours, and drying to prepare a cotton fabric with an angularly cross-linked slight gel structure; PB is 2-phosphonobutane-1,2,4-tricarboxylic acid; The volume ratio of the phytic acid solution to PB is 10:4; the phytic acid solution consists of phytic acid and deionized water; the mass fraction of the phytic acid solution is 6.5%; and the purity of the phytic acid is 40%.

[0044] Step 3, immersing the cotton fabric obtained in step 2 in a 12% dopamine hydrochloride solution for layer-by-layer assembly, the immersion time is 45 minutes, and drying the cotton fabric at 70°C for 2 hours, so that a layer of nano adhesive is formed on the surface of the internal fibers of the cotton fabric; immersing the dried cotton fabric in a 3.5% pyrrole solution, and dropping an initiator into the pyrrole solution to polymerize the pyrrole, and performing ultrasonic stirring for 2 hours; drying the obtained cotton fabric at 40°C for 2 hours, so as to obtain a layer-by-layer self-assembled antistatic / flame retardant fabric based on an angular cross-linking structure; The dopamine hydrochloride solution is composed of dopamine hydrochloride powder and deionized water; the initiator is ferric chloride solution with a concentration of 1 mol / L.

[0045] Example 6 The preparation method of the layer-by-layer self-assembled antistatic / flame-retardant fabric based on the angular cross-linked structure of the present invention is specifically implemented according to the following steps: Step 1, immersing cotton fabric in a mixed solution of DM-ammonium alginate solution for 60 minutes, and drying to prepare cotton fabric containing gel-like DM ammonium alginate; DM is dimethyl N,N-bis(2-hydroxyethylphosphoramide); The preparation process of dimethyl N,N-bis(2-hydroxyethylphosphoramide) is as follows: Tetrahydrofuran, dimethyl phosphite and diethanolamine were mixed in a volume ratio of 4:2:3, stirred for 1 hour, the white precipitate was filtered out and dried to obtain light yellow dimethyl N,N-bis(2-hydroxyethylphosphoramide); The volume ratio of ammonium alginate solution to DM is 20:1; the ammonium alginate solution is composed of ammonium alginate and deionized water; the mass fraction of the ammonium alginate solution is 5%; Step 2, immersing the cotton fabric obtained in step 1 in a mixed solution of PB-phytic acid solution for 6 hours, and drying to prepare a cotton fabric with an angularly cross-linked slight gel structure; PB is 2-phosphonobutane-1,2,4-tricarboxylic acid; The volume ratio of the phytic acid solution to PB is 10:5; the phytic acid solution consists of phytic acid and deionized water; the mass fraction of the phytic acid solution is 10%; and the purity of the phytic acid is 80%.

[0046] Step 3, immersing the cotton fabric obtained in step 2 in a 15% dopamine hydrochloride solution for layer-by-layer assembly, the immersion time is 60 minutes, and drying the cotton fabric at 80°C for 2 hours, so that a layer of nano adhesive is formed on the surface of the internal fibers of the cotton fabric; immersing the dried cotton fabric in a 5% pyrrole solution, and dropping an initiator into the pyrrole solution to polymerize the pyrrole, and performing ultrasonic stirring for 4 hours; drying the obtained cotton fabric at 80°C for 2 hours, so as to obtain a layer-by-layer self-assembled antistatic / flame retardant fabric based on an angular cross-linking structure; The dopamine hydrochloride solution is composed of dopamine hydrochloride powder and deionized water; the initiator is ferric chloride solution with a concentration of 1 mol / L.

[0047] The method of the present invention uses a composite material of dimethyl N, N-bis (2-hydroxyethyl phosphoramide) / ammonium alginate (DM ammonium alginate) to impart flame retardant properties to the insulating layer on the basis of isolating phytic acid. Secondly, 2-phosphonobutane-1,2,4-tricarboxylic acid is introduced into phytic acid to obtain phosphorus-containing polycarboxylic acid PB phytic acid, which is cross-linked with DM ammonium alginate to construct a "corner cross-linked" slight gel structure to enhance flame retardancy and durability. Subsequently, dopamine is used to bond pyrrole and ferroferric oxide layer by layer on the surface. Among them, dopamine can form a nano-adhesive layer on the surface of the internal fibers of the cotton fabric, enhance the bonding performance between the conductive material and the fabric, and realize the embedded structure construction of polypyrrole and cotton fabric.

[0048] The finishing of cotton fabrics uses the method of layer-by-layer impregnation self-assembly, with DM ammonium alginate for the first impregnation and phosphorus-containing polycarboxylic acid PB phytic acid for the second impregnation, so that the molecular chains between the two layers form angle crosslinking, and obtain the "angle crosslinking" molecular structure, which enhances the molecular chain bonding strength between the two layers of functional coatings. The third impregnation of cotton fabrics is to construct an embedded structure of polypyrrole and dopamine nano-adhesive agents on the fabric surface through chemical crosslinking to achieve the antistatic function of the fabric. In this process, three layer-by-layer impregnation processes are used, and the flame retardant and antistatic dual-functional finishing of cotton fabrics is completed through the two structural designs of "angle crosslinking" and embedded structure on the surface of cotton fabrics.

Claims

1. A method for preparing a layer-by-layer self-assembled antistatic / flame-retardant fabric based on an angular cross-linked structure, characterized in that: Specifically, the cotton fabric is flame-retarded by using gel-like DM ammonium alginate and composite flame retardant PB phytic acid to form a gel-like "angular cross-linked" three-dimensional structure, and the cotton fabric is anti-statically treated by using polypyrrole and cotton fabric embedded structure.

2. The method for preparing the layer-by-layer self-assembled antistatic / flame-retardant fabric based on the angular cross-linked structure according to claim 1, characterized in that: Follow the steps below to implement it: Step 1, immersing cotton fabric in a mixed solution of DM-ammonium alginate solution, and drying, to prepare cotton fabric containing gel-like DM ammonium alginate; Step 2, immersing the cotton fabric obtained in step 1 in a mixed solution of PB-phytic acid solution, and drying to prepare a cotton fabric with an angularly cross-linked slight gel structure; Step 3, immersing the cotton fabric obtained in step 2 in a dopamine hydrochloride solution to assemble layer by layer, and drying; immersing the cotton fabric in a pyrrole solution, and dropping an initiator into the pyrrole solution to polymerize the pyrrole, performing ultrasonic stirring, and drying to obtain a layer-by-layer self-assembled antistatic / flame retardant fabric based on an angular cross-linked structure.

3. The method for preparing the layer-by-layer self-assembled antistatic / flame-retardant fabric based on the angular cross-linked structure according to claim 2, characterized in that: In the step 1, the immersion time is 20-60 minutes, the ammonium alginate solution is composed of ammonium alginate and deionized water; the volume ratio of the ammonium alginate solution to DM is 10-20:1; and the mass fraction of the ammonium alginate solution is 2%-5%.

4. The method for preparing the layer-by-layer self-assembled antistatic / flame-retardant fabric based on the angular cross-linked structure according to claim 3, characterized in that: DM is dimethyl N, N-bis (2-hydroxyethyl phosphoramide); the preparation process of dimethyl N, N-bis (2-hydroxyethyl phosphoramide) is as follows: Tetrahydrofuran, dimethyl phosphite and diethanolamine were mixed in a volume ratio of 4:2:3, stirred for 1 hour, the white precipitate was filtered out and dried to obtain light yellow dimethyl N,N-bis(2-hydroxyethylphosphoramide).

5. The method for preparing the layer-by-layer self-assembled antistatic / flame-retardant fabric based on the angular cross-linked structure according to claim 2, characterized in that: In the step 2, PB is 2-phosphonobutane-1,2,4-tricarboxylic acid; the phytic acid solution is composed of phytic acid and deionized water; the volume ratio of the phytic acid solution to PB is 10:2-5; and the mass fraction of the phytic acid solution is 5%-10%.

6. The method for preparing the layer-by-layer self-assembled antistatic / flame-retardant fabric based on the angular cross-linked structure according to claim 2, characterized in that: In step 2, the immersion time is 20 minutes to 6 hours.

7. The method for preparing the layer-by-layer self-assembled antistatic / flame-retardant fabric based on the angular cross-linked structure according to claim 2, characterized in that: In step 3, the immersion time is 20-60 minutes. The drying temperature is 40°C-80°C, the drying time is 2h, and the ultrasonic time is 2-4h.

8. The method for preparing the layer-by-layer self-assembled antistatic / flame-retardant fabric based on the angular cross-linked structure according to claim 2, characterized in that: In step 3, the dopamine hydrochloride solution is composed of dopamine hydrochloride powder and deionized water; the concentration of the dopamine hydrochloride solution is 5%-15%; The initiator is a ferric chloride solution, and the concentration of the ferric chloride solution is 0.2 mol / L-1 mol / L; the concentration of the pyrrole solution is 1%-5%.

9. The layer-by-layer self-assembled antistatic / flame-retardant fabric prepared by the method for preparing the layer-by-layer self-assembled antistatic / flame-retardant fabric based on an angular cross-linked structure according to any one of claims 1 to 8.